Effect of Water, Sanitation, Handwashing, and Nutrition Interventions on Enteropathogens in Children 14 Months Old: A Cluster-Randomized Controlled Trial in Rural Bangladesh. (29th August 2020) - Grembi, Jessica A; Lin, Audrie; Karim, Md Abdul; Islam, Md Ohedul; Miah, Rana; Arnold, Benjamin F; McQuade, Elizabeth T Rogawski; Ali, Shahjahan; Rahman, Md Ziaur; Hussain, Zahir; Shoab, Abul K; Famida, Syeda L; et al.
Abstract: Background: We evaluated the impact of low-cost water, sanitation, and handwashing (WSH) and child nutrition interventions on enteropathogen carriage in the WASH Benefits cluster-randomized controlled trial in rural Bangladesh. Methods: We analyzed 1411 routine fecal samples from children 14 ± 2 months old in the WSH (n = 369), nutrition counseling plus lipid-based nutrient supplement (n = 353), nutrition plus WSH (n = 360), and control (n = 329) arms for 34 enteropathogens using quantitative polymerase chain reaction. Outcomes included the number of co-occurring pathogens; cumulative quantity of 4 stunting-associated pathogens; and prevalence and quantity of individual pathogens. Masked analysis was by intention-to-treat. Results: Three hundred twenty-six (99.1%) control children had 1 or more enteropathogens detected (mean, 3.8 ± 1.8). Children receiving WSH interventions had lower prevalence and quantity of individual viruses than controls (prevalence difference for norovirus: –11% [95% confidence interval CI, –5% to –17%]; sapovirus: –9% [95% CI, –3% to –15%]; and adenovirus 40/41: –9% [95% CI, –2% to –15%]). There was no difference in bacteria, parasites, or cumulative quantity of stunting-associated pathogens between controls and any intervention arm. Conclusions: WSH interventions were associated with fewer enteric viruses in children aged 14 months. Different strategies are needed to reduce enteric bacteria and parasites at this critical young age. Abstract : We evaluated the impact of water, sanitation, and handwashing (WSH) and nutrition interventions on enteropathogens in children in Bangladesh. WSH interventions were associated with fewer enteric viruses compared to controls. There was no difference in bacterial and protozoan pathogens for WSH or nutrition interventions.